NETWORK FORM OF MASTER'S PROGRAMMES: PROBLEMS OF COMPETENCE-BASED APPROACH IMPLEMENTATION - Valeriy I. Nikiforov; Mikhail M. Radkevich; Vadim V. Karmanov; Svetlana V. Karmanova (Высшее образование в России)
The article addresses the advantages and a number of problems of Master's training organization in a network form. Basing on network interaction, the project participants (four Russian universities) have designed the Basic educational program for Master's training in mechanical engineering. The partner universities have elaborated the unified methodological foundations for network basic educational program, the general principles for curricula development, measures for ensuring the academic mobility. The general organizational and methodological provisions are the following: full-time studies for all categories of students; mutual exchange of students between the universities cannot exceed one term; in the third semester students can choose the partner university to study; network training program should be implemented according to the principles of cooperation and the general methodological principles of educational process organization; the main types of students' activities are technology project activities, design and construction and research activity. As the network organization of the educational program is based on the competence approach, the universities faced the task to formulate the unified aggregated competences. The concerted list of aggregated competences includes three general and nine professional competences. The partner universities have to coordinate the conceptual fundamentals of student training in all partner universities.